PEMODELAN 3D MASJID DAARUT TAUHID BANDUNG MENGGUNAKAN TERRESTRIAL LASER SCANNER - Nata Kusumah, Adriand
The Daarut Tauhid Bandung Mosque has been renovated in 2015 has increased on building shape, architecture, and environmentally friendly concepts. These improvements make the new Daarut Tauhid Mosque in Bandung very comfortable. This increase must be maintained so that a 3D model of this mosque is needed that can show the shape of the building and the objects in it. This model can be used as a reference when building maintenance or when there is a reconstruction if there is damage due to a natural disaster. The 3D model can be produced using Terrestrial Laser Scanner (TLS) technology. The purpose of this research is to make a 3D model of Masjid Daarut Tauhid Bandung and find out the validity of the TLS measurements produced. The process used to produce 3D models of TLS technology is the stages of planning, data acquisition, and processing and presenting data. The processing of the data covers the georeferencing stages with direct georeferencing method, registration with cloud to cloud registration method, filtering, and making 3D models using manual method. The final result of this model is presented in a video that displays all parts of the 3D model that is produced. The resulting 3D model still has some disadvantages, that is the calligraphy on the outside of the mosque still does not represent the actual form of calligraphy, some parts of the mosque have little reflectivity that cannot be obtained by TLS, and there are parts of the mosque's roof that are not caught by TLS due to its position too high. The registration process has a 0.010 m RMS. The results of the geometric validity in the maximum size difference between TLS and the laser distance meter / measuring tape is 0.016 m with an average of ± 0.005 m.